2008
DOI: 10.1111/j.1440-1681.2007.04856.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Endothelin Receptor Antagonist Cpu0213, and Its Modulation by Rifampin, on Cardiac and Vascular Tissue Following Chronic Isoproterenol Treatment

Abstract: 1. The aim of the present study was to investigate the effects of the endothelin (ET) receptor antagonist CPU0213 on cardiac and vascular tissues after impairment by chronic isoproterenol treatment. Because rifampin reduces plasma concentrations of CPU0213, the modulation of the effects of CPU0213 by rifampin was also investigated. 2. Thirty rats were randomly divided into five groups as follows: (i) control; (ii) isoproterenol treated (1 mg/kg, s.c., for 10 days); (iii) isoproterenol treated with a single inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, the benefits of CPU0213 plus erythromycin to the myocardium were not significantly different from CPU0213 alone 13 . In this study we designed a low dose of CPU0213, 20 mg/kg (s.c.) against 30 mg/kg (s.c.) in the study by Luo et al 14 , in which rifampicin caused a decline from 2.795 to 0.939 μg/ml, and a reduction in plasma concentration did not affect the effects on abnormality of FKBP12.6, SERCA2a and ET A , but a mild modulation of effects on the improved vascular activity. Effects of CPU0213 in the two studies, however, did not respond positively to a fluctuation of plasma levels by the CYP3A inhibitor erythromycin.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the benefits of CPU0213 plus erythromycin to the myocardium were not significantly different from CPU0213 alone 13 . In this study we designed a low dose of CPU0213, 20 mg/kg (s.c.) against 30 mg/kg (s.c.) in the study by Luo et al 14 , in which rifampicin caused a decline from 2.795 to 0.939 μg/ml, and a reduction in plasma concentration did not affect the effects on abnormality of FKBP12.6, SERCA2a and ET A , but a mild modulation of effects on the improved vascular activity. Effects of CPU0213 in the two studies, however, did not respond positively to a fluctuation of plasma levels by the CYP3A inhibitor erythromycin.…”
Section: Discussionmentioning
confidence: 81%
“…The effects of CPU0213 were investigated while exposed to the enzyme‐inducing drug rifampicin. It was found that it caused a reduction in plasma levels but had no effect on the heart; however; the relationship of the effects of the endothelin receptor antagonist CPU0213 in response to plasma levels has not been fully clarified 14 . It is uncertain whether erythromycin, as the inhibitor of CYP3A, by raising blood concentrations of CPU0213, augments its benefits on stress‐induced cardiac injury by improving further abnormal leptin and the calcium modulating protein FKBP12.6 15 …”
Section: Introductionmentioning
confidence: 99%
“…However, the benefits of CPU0213 plus erythromycin to the myocardium were not significantly different from CPU0213 alone. [13] In this study we designed a low dose of CPU0213, 20 mg/kg (s.c.) against 30 mg/kg (s.c.) in the study by Luo et al [14] , in which rifampicin caused a decline from 2.795 to 0.939 mg/ml, and a reduction in plasma concentration did not affect the effects on abnormality of FKBP12.6, SERCA2a and ET A , but a mild modulation of effects on the improved vascular activity. Effects of CPU0213 in the two studies, however, did not respond positively to a fluctuation of plasma levels by the CYP3A inhibitor erythromycin.…”
Section: Discussionmentioning
confidence: 82%
“…It was found that it caused a reduction in plasma levels but had no effect on the heart; however; the relationship of the effects of the endothelin receptor antagonist CPU0213 in response to plasma levels has not been fully clarified. [14] It is uncertain whether erythromycin, as the inhibitor of CYP3A, by raising blood concentrations of CPU0213, augments its benefits on stress-induced cardiac injury by improving further abnormal leptin and the calcium modulating protein FKBP12.6. [15] We hypothesized that isoprenaline developed cardiac hypertrophy and insufficiency by upregulating the endothelin A receptor (ET A ) and leptin to downregulate FKBP12.6, therefore compromising cardiac function, and the endothelin receptor antagonist may counteract these abnormalities in the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic medication of isoproterenol mimicking a stress status related to an increase in sympathetic outflow, causes an impairment of vascular activity which is effectively reversed by endothelin receptor antagonist CPU0213 45. The abnormal vascular activity is characterized by an increase in expression of ETA, NOX, and MMP9 in the vasculature which are attenuated by either CPU0213 a blockade on ET receptors and an antioxidant activity by aminoguanidine.…”
Section: Hypertension and Stress-induced Vascular Abnormalitiesmentioning
confidence: 99%